2018
DOI: 10.3389/fimmu.2018.02908
|View full text |Cite
|
Sign up to set email alerts
|

HRV16 Impairs Macrophages Cytokine Response to a Secondary Bacterial Trigger

Abstract: Human rhinovirus is frequently seen as an upper respiratory tract infection but growing evidence proves the virus can cause lower respiratory tract infections in patients with chronic inflammatory lung diseases including chronic obstructive pulmonary disease (COPD). In addition to airway epithelial cells, macrophages are crucial for regulating inflammatory responses to viral infections. However, the response of macrophages to HRV has not been analyzed in detail. We used in vitro monocyte-derived human macropha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 41 publications
0
7
0
Order By: Relevance
“…We found that this was not the case, further emphasising that HRV16 specifically affected the internalisation step. These results are important in the context of COPD where HRV is frequently isolated [20] and, together with other defective functions like cell activation [13,[22][23][24], could be one of the explanations as to why patients show bacterial outgrowths post-HRV infection [13,19]. Phagocytosis is strictly dependent on actin polymerisation (for review, Refs.…”
Section: Discussionmentioning
confidence: 95%
See 2 more Smart Citations
“…We found that this was not the case, further emphasising that HRV16 specifically affected the internalisation step. These results are important in the context of COPD where HRV is frequently isolated [20] and, together with other defective functions like cell activation [13,[22][23][24], could be one of the explanations as to why patients show bacterial outgrowths post-HRV infection [13,19]. Phagocytosis is strictly dependent on actin polymerisation (for review, Refs.…”
Section: Discussionmentioning
confidence: 95%
“…However, mounting evidence shows that HRV can infect the lower respiratory tract in patients with chronic inflammatory diseases including chronic obstructive pulmonary disease (COPD) driving disease exacerbations [17][18][19][20]. How HRV disrupts macrophage/monocyte functions remains unknown, but HRV was reported to induce a defective secondary response in macrophages [13,[22][23][24]. How HRV disrupts macrophage/monocyte functions remains unknown, but HRV was reported to induce a defective secondary response in macrophages [13,[22][23][24].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In COPD, rhinovirus specifically has been shown to impair bacterial phagocytosis by macrophages [ 34 ]. Others, using in vitro experiments, have shown alveolar macrophages are less able to mount an immune response to bacteria following HRV infection [ 35 , 36 ]. Viruses clearly play a role in the airway, the most significant of which may be their interaction with immune defense and bacteria.…”
Section: Discussionmentioning
confidence: 99%
“…Unlike the here described RV-induced priming effect, infection of MΦ with human rhinovirus instead of RV has been reported to impair the cytokine response to LPS ( 50 ). Thus, the type of virus seems to be crucial for the outcome of a secondary bacterial stimulation and no predictions can be made.…”
Section: Discussionmentioning
confidence: 71%